Triamidoamine-uranium(IV)-stabilized terminal parent phosphide and phosphinidene complexes - Gardner, Benedict M.; Balázs, Gábor; Scheer, Manfred; Tuna, Floriana; McInnes, Eric J.L.; McMaster, Jonathan; Lewis, William; Blake, Alexander J.; Liddle, Stephen T. (Wiley-VCH Verlag, 2014)
Reaction of [U(TrenTIPS)(THF)][BPh4] (1; TrenTIPS=N{CH2CH2NSi(iPr)3}3) with NaPH2 afforded the novel f-block terminal parent phosphide complex [U(TrenTIPS)(PH2)] (2; U–P=2.883(2) Å). Treatment of 2 with one equivalent of KCH2C6H5 and two equivalents of benzo-15-crown-5 ether (B15C5) afforded the unprecedented metal-stabilized terminal parent phosphinidene complex [U(TrenTIPS)(PH)][K(B15C5)2] (4; U[DOUBLE BOND]P=2.613(2) Å). DFT calculations reveal a polarized-covalent U[DOUBLE BOND]P bond with a Mayer bond order of 1.92.